Development Of Design Of Experiment (DOE) Software, For 2k Factorial Design (where k = 2 and 3) - Mohd Hamzah, Mohd Salzahrin (Universiti Sains Malaysia, 2006)
Design of Experiment is a technique for understanding a process, studying the impact of potential variable of factors affecting the process and thereby providing the idea and insight for continuous quality improvement possibilities. Factorial design is one of the Design of Experiment methods to design an experiment where we have more than two factors. This thesis will show the usage of DOE and the statistical methods to run the experiment for factorial designs. The C++ Builder software program is also one of the tools in order to build this software. Research on DOE is very helpful in order to understand more on the topic so that this software will meet the objective sooner after the software is ready to use. With this software, it will help student in engineering courses to understand more about DOE especially on factorial design. Moreover, this software will be the basic tool for them to start with.